De veranderende bestuurscultuur in wetenschap en universiteit in de jaren zeventig en tachtig - Baneke, David (BMGN - Low Countries Historical Review, 2014)
Astronomy after Oort: The Changes in Administrative Culture in Science and the Universities in the 1970s and 1980s In the early 1970s Dutch universities were reformed, while scientific research was faced with new social and political demands. A decade later science and university policy changed again, with increasing roles for market pressure and competition. These developments might seem opposed, but in this paper David Baneke will argue that in fact there was great continuity, both concerning the backgrounds of the policy and the practical consequences. Their goal was to cope with the rapid increase in scale and the costs of science, to open up closed elitist networks, and to counter inefficiency and arbitrary spending. The pressure to reform came both from policy makers and from within the universities themselves. In all cases the changes resulted in professional management structures and an increase in bureaucracy. In this paper, Baneke will analyse these developments from the perspective of the internationally prominent Dutch astronomical community, which experienced a serious crisis in 1970 in which every part of the disciplinary infrastructure was reconsidered. Rond 1970 werden de Nederlandse universiteiten grondig hervormd en werden er nieuwe maatschappelijke eisen gesteld aan wetenschappelijk onderzoek. In de jaren tachtig werden die hervormingen deels teruggedraaid, terwijl marktwerking en concurrentie een grotere plaats kregen in het wetenschapsbeleid. Die ontwikkelingen lijken tegenstrijdig, maar in dit artikel betoogt David Baneke dat er een grote continuïteit bestaat, zowel in de achtergronden van het beleid als in de uitwerking in de wetenschappelijke praktijk. Het waren pogingen om schaalvergroting en kostenstijging beheersbaar te houden, gesloten regenteske netwerken open te breken en willekeur en inefficiëntie te bestrijden. De druk om te veranderen kwam zowel van de overheid als uit de universiteiten zelf. Het gevolg was in alle gevallen een sterke groei van professionele managementstructuren en bureaucratie. Baneke analyseert deze ontwikkelingen vanuit het perspectief van de internationaal prominente Nederlandse astronomische gemeenschap, die rond 1970 een ernstige crisis doormaakte waarin de hele disciplinaire structuur ter discussie stond.